A mobile application that allows children in the early childhood to program robots - Ramírez Benavides, Kryscia Daviana (2016)
Children born in the Information Age are digital natives; this characteristic should be exploited to improve the learning process through the use of technology. This paper addresses the design, construction, and evaluation process of TITIBOTS, a programming assistance tool for mobile devices that allows children in the early childhood to create programs and execute them using robots. We present the results of using TITIBOTS in different scenarios with children between 4 and 6 years old. The insight obtained in the development and evaluation of the tool could be useful when creating applications for children in the early childhood. The results were promising; children liked the application and were willing to continue using it to program robots to solve specific tasks, developing the skills of the 21st century.